PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP KINERJA PELAYANAN PUBLIK DI KANTOR DESA TAMALANREA - Nurfahmita, Nurfahmita; Nurlinda, Nurlinda; Haekal Ramadani; Juniarti Iryani , Juniarti Iryani (Nusantara Hasana Journal, 2025)
This study aims to examine the impact of information technology utilization on the quality of public services at the Tamalanrea Village Office. A descriptive quantitative approach was used, with data collected through the distribution of structured questionnaires to two respondent groups: village office staff and community members who use public services. The total number of respondents was 23, and the data were analyzed using a Likert scale to measure the influence of information technology on indicators of public service performance. The results indicate that the use of information technology has a significant effect on improving service efficiency, accessibility, and community satisfaction. However, challenges remain, including technical issues, incomplete technological infrastructure, and limited public understanding of digital services. This study emphasizes the importance of continuous digital training, infrastructure development, and strategic policy support to optimize the benefits of digital-based public services. The findings are expected to contribute to the development of more modern and responsive e-Government services at the village level. This research also provides valuable insights for policymakers, local governments, and practitioners in strengthening public service governance through digital innovation and participatory approaches.